A graphyne-like porous carbon-rich network synthesized via alkyne metathesis. Issue 33 (8th August 2017) - Wu, Bin; Li, Manrong; Xiao, Shuning; Qu, Yangkun; Qiu, Xiaoyan; Liu, Taifeng; Tian, Fenghui; Li, Hexing; Xiao, Shengxiong
Abstract : Alkyne metathesis was applied to yield a sp 2 /sp hybridized graphyne-like porous carbon-rich network material with tilted 3D channels and showed selective absorption of CO2 over N2 . Abstract : The synthesis of graphyne has been considered challenging, especially when it comes to adopting new topologies and obtaining thinner layers. Herein, we report the synthesis and characterization of a graphyne-like porous carbon-rich network via alkyne metathesis reactions, which resulted in a sp 2 /sp hybridized 2D thin film structure with a layer to layer distance of 0.37 nm. This graphyne-like porous carbon-rich network is an n-type semiconductor with a low work function of 3.9 eV and a reduction potential of −0.54 V vs. SHE, which could be applied as an excellent reducing agent for metal electroless deposition. In addition, this material has a narrow pore size distribution of 2 to 4 nm, a high surface area of 675 m 2 g −1 and a large pore volume of 0.795 cm 3 g −1 favoring gas adsorption. It shows the selective absorption of CO2 over N2 owing to the strong affinity between CO2 and the carbon–carbon triple bond.